Desk review report on policy priorities and opportunities, and social equity considerations - Rebecca Sarku; Stephen Whitfield (2023)
This document will be a reference point in engaging stakeholders to influence policy through the iFEED process. The stakeholders identified will be grouped into working groups based on ratings on areas of interest and positions to integrate iFEED results to influence policies at various levels. Work Package 3 will work closely with stakeholders to organise stakeholder engagements for iFEED by convening and coordinating the activities of working groups. Stakeholders will have the opportunity to prioritise policies, provide information on opportunities to make input into the iFEED process, and provide feedback on iFEED results. The objectives will be achieved through regular (monthly) online meetings with stakeholders.